2016
DOI: 10.1103/physrevd.93.064072
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotically Lifshitz spacetimes with universal horizons in (1+2) dimensions

Abstract: Hořava gravity theory possesses global Lifshitz space as a solution and has been conjectured to provide a natural framework for Lifshitz holography. We derive the conditions on the two derivative Hořava gravity Lagrangian that are necessary for static, asymptotically Lifshitz spacetimes with flat transverse dimensions to contain a universal horizon, which plays a similar thermodynamic role as the Killing horizon in general relativity. Specializing to z = 2 in 1 + 2 dimensions, we then numerically construct suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 37 publications
(90 reference statements)
1
30
0
Order By: Relevance
“…Since they were first discovered in [202,215], universal horizons have been studied intensively, and already attracted lots of attention. These include universal horizons in static spacetimes [123,[218][219][220][221][222][223][224][225][226][227][228][229][230][231][232][233][234], and the ones with rotation [217,235,236] 25 . In particular, it was showed that universal horizons exist in the 24 To avoid theČerenkov effects, in the khronometric theory, or more general, in the Einstein-aether theory, c φ is required to be no less than the speed of light c φ ≥ c [203].…”
Section: )mentioning
confidence: 99%
“…Since they were first discovered in [202,215], universal horizons have been studied intensively, and already attracted lots of attention. These include universal horizons in static spacetimes [123,[218][219][220][221][222][223][224][225][226][227][228][229][230][231][232][233][234], and the ones with rotation [217,235,236] 25 . In particular, it was showed that universal horizons exist in the 24 To avoid theČerenkov effects, in the khronometric theory, or more general, in the Einstein-aether theory, c φ is required to be no less than the speed of light c φ ≥ c [203].…”
Section: )mentioning
confidence: 99%
“…Recently, [23] studied asymptotic Lifshitz solutions for the three-dimensional case (D = 2). They imposed the following condition of analyticity on the power series solutions around infinity…”
Section: Lifshitz Asymptotic Solutionsmentioning
confidence: 99%
“…Regarding the applications to holography, static asymptotically Lifshitz UHs in (2+1) dimensions were analyzed in [19]. It was shown that these UHs possess a first law of the form dM ∝ T UH dP UH , in analogy with their static (2+1) dimensional AdS counterparts [see Eq.…”
Section: Discussionmentioning
confidence: 99%
“…We are then led to the condition that u a be normal to the universal horizon. As discussed in [19], this ensures that no additional boundary term is needed in the action when the inner boundary is a UH, and moreover that the contributions to the on-shell Hamiltonian (23) from the UH vanish. Therefore the expression of the Hamiltonian is unaffected by the presence of a UH, and the definition of the mass remains the same.…”
Section: Universal Horizonsmentioning
confidence: 97%
See 1 more Smart Citation